Intermetallic compound reinforced gear shift friction plate material and preparation method

By adding Cr, La2O3, composite reinforced phase (Fe3Al+TiC) and composite lubricated phase (NiMoO4+nickel-clad graphite balls) to the high-aluminum bronze matrix, the problem of insufficient friction and wear performance of high-aluminum bronze under high temperature conditions is solved, and the efficient anti-wear and lubricating performance of the material is improved.

CN118773475BActive Publication Date: 2025-04-18CHINA NORTH VEHICLE RES INST
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202410707490.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-03
Publication Date
2025-04-18
Estimated Expiration
2044-06-03

AI Technical Summary

Technical Problem

The friction and wear performance of high-aluminum bronze under high temperature conditions is insufficient, resulting in a decrease in heat resistance, friction performance and service life.

Method used

Cr and La2O3 were added in a high-aluminum bronze matrix, and a composite reinforced phase (Fe3Al+TiC) and a composite lubricated phase (NiMoO4+nickel-clad graphite ball) were prepared to improve the material's wear resistance and lubricating properties.

Benefits of technology

Through the synergistic action of the composite reinforced phase and the composite lubricated phase, the friction coefficient and wear rate of the material are significantly reduced, and the wear resistance and service life are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118773475B_ABST
    Figure CN118773475B_ABST
Patent Text Reader

Abstract

The present invention relates to a gear shift friction plate material reinforced by an intermetallic compound and a preparation method thereof, belonging to the technical field of copper alloys. 3 Al+TiC) and composite lubricating phase (NiMoO 4 + nickel-coated graphite balls), a composite material with excellent mechanical and tribological properties can be obtained. 3 The composite strengthening phase composed of Al and TiC has a high mixing uniformity and surface chemical energy after high-energy ball milling and high-temperature sintering, and the interface bonding strength with the high-aluminum bronze matrix is ​​greatly improved. In addition, TiC can also 3 Al has a strengthening effect on the matrix. When dispersed in the high-aluminum bronze matrix, it can weaken the adhesive wear mechanism and significantly improve the wear resistance of the material. 4 At high temperatures, a lubricating film is formed on the friction surface to reduce the adhesive wear mechanism, and the nickel-coated graphite balls reduce the damage of hard wear debris to the friction surface to reduce the abrasive wear mechanism. Ultimately, the material maintains a low friction coefficient and wear rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an intermetallic compound reinforced gear shift friction plate material and a preparation method thereof, belonging to the technical field of copper alloys. Background Art

[0002] High aluminum bronze has high strength and hardness, excellent corrosion resistance and oxidation resistance, and is widely used in friction parts such as shift friction plates, sliding bearings, screws, gears, copper sleeves, and sealing rings. However, the adhesive wear of high aluminum bronze gradually intensifies during the friction and wear process under high temperature conditions, the friction coefficient fluctuates greatly, and the wear rate increases rapidly, resulting in a significant decrease in the heat resistance, friction performance, and service life of the shift friction pair. Therefore, the wear resistance and wear mechanism of high aluminum bronze shift friction plate materials need to be further optimized.

[0003] Patent CN105088004A improves the friction and wear properties of aluminum bronze by adding elements such as Cr and Si; Patent CN112195361A improves the strength and wear resistance of the copper matrix by adding elements such as Zn and Ti; Patent CN104388749A reduces the friction coefficient and wear rate of aluminum bronze by adding elements such as Ce and B. However, the addition of the above alloying elements is mainly to strengthen the matrix through mechanisms such as grain refinement. Due to the lack of effective strengthening phases and lubricating phases, the improvement effect on wear resistance and wear mechanism is limited. Patent CN108517435B significantly reduces the friction coefficient by adding graphene, carbon nanotubes and lead as lubricants to the copper matrix. However, the cost of using graphene is high, and lead will cause serious pollution to the environment. In addition, the above process is relatively complicated, and the effect of reducing the adhesive wear mechanism is relatively small. Patent CN106086585B reduces the friction coefficient and wear rate by adding graphite and Al2O3 to the copper-iron alloy matrix, but the interface bonding force between graphite and Al2O3 and the matrix is ​​weak. When the content of graphite and Al2O3 is relatively high, the uniformity of the material's organization, mechanical strength and wear resistance will decrease. Patent CN112831685A adds SiC and Fe3Al to the copper-iron alloy for strengthening, but its matrix only contains two elements, Cu and Fe, so the mechanical properties, corrosion resistance, lubrication and wear resistance of the material are relatively low. At the same time, the bonding force between SiC and the matrix is ​​poor, and when its content is high, cracks are prone to initiation and expansion. The above research results show that the traditional strengthening phase and lubrication phase have limited effect on the improvement of the friction performance of the high-aluminum bronze matrix, and when the content is high, it will have an adverse effect on the uniformity of the material's organization and mechanical strength; at the same time, the modification effect of a single strengthening phase or lubrication phase is limited, and the strengthening phase needs to be matched with the lubrication phase to produce a coupling effect in order to reduce wear while maintaining a stable friction coefficient. Therefore, it is necessary to study new composite strengthening phase and lubricating phase formulas and material preparation methods to further improve the friction and wear properties of high aluminum bronze alloys.

[0004] Studies have shown that adding alloying elements to copper alloys can improve hardness and strength, but there is no report on compounding Cr and Y2O3 to improve the wear resistance of high aluminum bronze. At the same time, both Fe3Al and TiC have high hardness, and TiC can strengthen Fe3Al. Some researchers have studied the friction performance of Fe3Al and TiC, but there is no report on preparing a composite strengthening phase (Fe3Al+TiC) and adding it to high aluminum bronze to enhance the wear resistance. In addition, NiMoO4 will form a lubricating film on the friction surface at high temperature, keeping the friction coefficient low and stable. Nickel-coated graphite balls can reduce the damage of hard wear debris to the friction surface. The existing technology has realized the use of NiMoO4 and nickel-coated graphite balls, but there is no research on preparing a composite lubricating phase (NiMoO4+nickel-coated graphite balls) to improve the lubrication performance of high aluminum bronze. There is also no report on adding a composite strengthening phase (Fe3Al+TiC) and a composite lubricating phase (NiMoO4+nickel-coated graphite balls) to a copper-iron alloy and precisely regulating their mutual coupling properties. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide an intermetallic compound reinforced shift friction plate material and preparation method. Cr and La2O3 are added to the high aluminum bronze matrix, and the mechanical properties of the matrix are improved by controlling the content; a composite strengthening phase (Fe3Al+TiC) is prepared and added to improve the wear resistance of the high aluminum bronze; a composite lubricating phase (NiMoO4+nickel-coated graphite balls) is prepared and added to improve the lubrication performance of the high aluminum bronze; a composite strengthening phase (Fe3Al+TiC) and a composite lubricating phase (NiMoO4+nickel-coated graphite balls) are added to the high aluminum bronze matrix at the same time, so that the adhesive wear reduction effect of (Fe3Al+TiC) and the abrasive wear reduction effect of (NiMoO4+nickel-coated graphite balls) are coupled to each other, thereby reducing the friction coefficient and wear rate of the material at the same time.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows.

[0007] The invention discloses an intermetallic compound reinforced gear shift friction plate material. Taking the total mass of the material as 100%, the components and their mass percentages are as follows: 80.0% to 92.0% of a high-aluminum bronze matrix, 3.0% to 8.0% of a composite reinforcement phase, and 5.0% to 12.0% of a lubricating phase. The composite reinforcement phase is formed by compounding Fe3Al and TiC through high-energy ball milling, and the mass fraction of Fe3Al in the composite reinforcement phase is 60.0% to 80.0%, and the mass fraction of TiC is 20.0% to 40.0%. The composite lubricating phase is formed by combining NiMoO4 and nickel-coated graphite balls, and the mass fraction of NiMoO4 in the composite lubricating phase is 40.0% to 60.0%, and the mass fraction of nickel-coated graphite balls is 40.0% to 60.0%. The material is obtained by ball milling and hot-pressing sintering of an aluminum bronze matrix, a composite reinforcement phase, and a composite lubricating phase.

[0008] Preferably, taking the total mass of the material as 100%, the components and their mass percentages are: Cu63.0% to 75.0%, Al 9.0% to 13.0%, Ni 1.0% to 2.5%, Fe 2.5% to 4.0%, Mn 0.5% to 1.5%, Cr 0.3% to 1.0%, Y2O3 0.3% to 1.0%, composite strengthening phase 3.0% to 8.0%, and composite lubrication phase 5.0% to 12.0%.

[0009] Preferably, the mesh size of the composite reinforcement phase powder is 200-300 meshes.

[0010] Preferably, the mesh size of the NiMoO4 powder is 200-300 meshes.

[0011] Preferably, the particle size of the nickel-coated graphite balls is 10 to 30 μm.

[0012] A method for preparing the intermetallic compound reinforced shift friction plate material of the present invention comprises the following steps:

[0013] (1) Fe3Al and TiC powders are mixed and wet-milled under inert gas protection, with a ball-to-material ratio of 3:1 to 4:1, a rotation speed of 250 to 350 r / min, and a ball milling time of 8 to 12 h to obtain a mixed powder; the mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1 Pa, sintering temperature is 1100-1300℃, holding time is 5-10min, after sintering, the furnace is cooled, and the obtained block is ground under the protection of inert gas to obtain composite strengthening phase powder;

[0014] (2) mixing a high aluminum bronze matrix, a composite strengthening phase powder and a composite lubricating phase powder, and ball milling them under inert gas protection, with a ball-to-material ratio of 1:1 to 2:1, a rotation speed of 150 to 200 r / min, and a ball milling time of 8 to 10 h to obtain a mixed powder;

[0015] (3) The mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1 Pa, the sintering temperature is 800-850°C, the sintering pressure is 35-40MPa, the holding time is 10-20min, and the furnace is cooled after sintering to obtain an intermetallic compound reinforced shift friction plate material.

[0016] Preferably, in step (1), the heating rate is 100-150° C. / min.

[0017] Preferably, in step (1), during grinding, the ball-to-material ratio is 1:1-2:1, the rotation speed is 100-150 r / min, and the grinding time is 6-8 h.

[0018] Preferably, in step (1), during grinding, the grinding pot and the grinding balls are both made of tungsten carbide cemented carbide.

[0019] Preferably, in step (1), during grinding, the grinding is stopped every 5 minutes and then continued after stopping for 3 minutes.

[0020] Preferably, in step (2), during ball milling, both the grinding jar and the grinding balls are made of tungsten carbide cemented carbide.

[0021] Preferably, in step (2), during ball milling, the mill is stopped every 10 minutes and then continued to run after stopping for 2 minutes.

[0022] Preferably, in step (3), during sintering, the heating rate is 100 to 150° C. / min.

[0023] Beneficial Effects

[0024] 1. The present invention provides a shift friction plate material reinforced by an intermetallic compound. The material is prepared by preparing a composite strengthening phase (Fe3Al+TiC) so that TiC can strengthen Fe3Al, thereby obtaining a mixed powder with high hardness, dispersion and surface chemical energy. At the same time, after the composite strengthening phase (Fe3Al+TiC) is added to the high-aluminum bronze matrix, the plowing and peeling effects of the contact surface can be reduced by the pinning mechanism without affecting the strength, thereby improving the wear resistance and service life. The ratio of Fe3Al to TiC will have a significant impact on the comprehensive performance of the material. If Fe3Al is too little and TiC is too much, the material will cause a decrease in mechanical properties due to decreased interface wettability and excessive impurities; if Fe3Al is too much and TiC is too little, it is difficult to effectively improve the wear resistance of the material. Compared with high-aluminum bronze with commonly used strengthening phases such as Al2O3, the present invention accurately controls the content of Fe3Al and TiC to make the material have both high mechanical properties and wear resistance.

[0025] 2. The present invention provides a shift friction plate material enhanced by an intermetallic compound. The friction material forms a lubricating film on the friction surface of NiMoO4 at high temperature by adding a composite lubricating phase (NiMoO4+nickel-coated graphite balls) to a high-aluminum bronze matrix to reduce the adhesive wear mechanism. At the same time, the nickel-coated graphite balls reduce the damage of hard wear debris to the friction surface to reduce the abrasive wear mechanism, thereby improving the friction reduction performance of the matrix under extreme braking high-temperature conditions. The content of NiMoO4 and nickel-coated graphite balls will have a significant impact on the material properties. If there is too much NiMoO4 and too little nickel-coated graphite balls, the material will have a decrease in strength and wear resistance due to decreased internal bonding force and excessive grain boundary impurities; if there is too little NiMoO4 and too much nickel-coated graphite balls, it is difficult to effectively improve the lubrication performance of the material under high-temperature conditions. Compared with copper-iron alloys that add common lubricating phases such as graphite, the present invention has a lower and more stable friction coefficient under high-temperature conditions by accurately controlling the content of NiMoO4 and nickel-coated graphite balls.

[0026] 3. The present invention provides a shift friction plate material reinforced by an intermetallic compound, wherein the material improves the anti-friction and anti-wear properties of the material by simultaneously adding a composite reinforcement phase (Fe3Al+TiC) and a composite lubricating phase (NiMoO4+nickel-coated graphite balls) to a high-aluminum bronze matrix. Compared with a material containing only one added phase, the present invention achieves the coupling of lubrication and anti-friction properties by accurately controlling the content of the composite reinforcement phase and the composite lubricating phase, so that the material has both a low friction coefficient and a wear rate.

[0027] 4. The present invention provides an intermetallic compound reinforced shift friction plate material, in which the composite reinforcement phase (Fe3Al+TiC) is prepared by high-energy ball milling and high-temperature sintering of Fe3Al powder and TiC powder. High-energy ball milling and high-temperature sintering promote the mutual dissolution of Fe3Al and TiC, so that TiC has a strengthening effect on Fe3Al. At the same time, the surface chemical energy of Fe3Al powder and TiC powder is greatly improved, and the bonding force with the matrix interface is stronger, thereby significantly improving the wear resistance of the material. The mass ratio of Fe3Al powder and TiC powder, high-energy ball milling and high-temperature sintering process have been obtained through multiple experiments, which can improve the uniformity and surface chemical energy of the composite reinforcement phase, making it easier to tightly bond with the high-aluminum bronze alloy interface during hot pressing sintering.

[0028] 5. The present invention provides a shift friction plate material reinforced by an intermetallic compound, wherein the material is prepared by adding Cr to a high aluminum bronze matrix to produce a solid solution strengthening effect, and Y2O3 is added to produce a dispersion strengthening effect. Compared with the existing matrix strengthening technology, the present invention combines solid solution strengthening with dispersion strengthening by accurately controlling the relative content of Cr and Y2O3, so that the material has excellent structural uniformity, hardness and strength.

[0029] 6. The present invention provides a shift friction plate material reinforced by an intermetallic compound, wherein the material has a hardness of 192 to 211 HV, a compressive strength of 893 to 1005 MPa, and a bending strength of 755 to 883 MPa. The material has a low wear rate, a low and stable friction coefficient, and good comprehensive performance.

[0030] 7. The present invention provides a method for preparing an intermetallic compound-enhanced shift friction plate material. The preparation process of the present invention is simple, and the targeted regulation of material properties can be achieved by adjusting the formula and process. At the same time, the present invention is low-cost and environmentally friendly, and can be used for friction parts under harsh working conditions such as sliding bearings, bushings, and sliders, and has a relatively broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Flow chart of the preparation method of the material described in the embodiment of the present invention. DETAILED DESCRIPTION

[0032] The present invention will be further described in detail below in conjunction with specific embodiments.

[0033] A shift friction plate material reinforced by an intermetallic compound, with the total mass of the material being 100%, the components and their mass percentages being: 80.0% to 92.0% of a high-aluminum bronze matrix, 3.0% to 8.0% of a composite reinforcement phase, and 5.0% to 12.0% of a composite lubricating phase; wherein the composite reinforcement phase is composited by Fe3Al and TiC, the mass fraction of Fe3Al in the composite reinforcement phase is 60.0% to 80.0%, and the mass fraction of TiC is 20.0% to 40.0%; the composite lubricating phase is composited by NiMoO4 and nickel-coated graphite balls, the mass fraction of NiMoO4 in the composite lubricating phase is 40.0% to 60.0%, and the mass fraction of nickel-coated graphite balls is 40.0% to 60.0%; the material is obtained by ball milling and hot pressing sintering of an aluminum bronze matrix, a composite reinforcement phase, and a composite lubricating phase.

[0034] Preferably, taking the total mass of the material as 100%, the components and their mass percentages are: Cu63.0% to 75.0%, Al 9.0% to 13.0%, Ni 1.0% to 2.5%, Fe 2.5% to 4.0%, Mn 0.5% to 1.5%, Cr 0.3% to 1.0%, Y2O3 0.3% to 1.0%, composite strengthening phase 3.0% to 8.0%, and composite lubrication phase 5.0% to 12.0%.

[0035] Preferably, the mesh size of the composite reinforcement phase powder and the NiMoO4 powder is 200-300 meshes.

[0036] Preferably, the particle size of the nickel-coated graphite balls is 10 to 30 μm.

[0037] like Figure 1 As shown, a method for preparing an intermetallic compound reinforced shift friction plate material comprises the following steps:

[0038] (1) Fe3Al and TiC powders are mixed and wet-milled under inert gas protection, with a ball-to-material ratio of 3:1 to 4:1, a rotation speed of 250 to 350 r / min, and a ball milling time of 8 to 12 h to obtain a mixed powder; the mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1 Pa, sintering temperature is 1100-1300℃, holding time is 5-10min, after sintering, the furnace is cooled, and the obtained block is ground under the protection of inert gas to obtain composite strengthening phase powder;

[0039] (2) mixing a high aluminum bronze matrix, a composite strengthening phase powder and a composite lubricating phase powder, and ball milling them under inert gas protection, with a ball-to-material ratio of 1:1 to 2:1, a rotation speed of 150 to 200 r / min, and a ball milling time of 8 to 10 h to obtain a mixed powder;

[0040] (3) The mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1 Pa, the sintering temperature is 800-850°C, the sintering pressure is 35-40MPa, the holding time is 10-20min, and the furnace is cooled after sintering to obtain an intermetallic compound reinforced shift friction plate material.

[0041] Preferably, in step (1), the heating rate is 100-150° C. / min.

[0042] Preferably, in step (1), during grinding, the ball-to-material ratio is 1:1-2:1, the rotation speed is 100-150 r / min, and the grinding time is 6-8 h.

[0043] Preferably, in step (1), during grinding, the grinding pot and the grinding balls are both made of tungsten carbide cemented carbide.

[0044] Preferably, in step (1), during grinding, the grinding is stopped every 5 minutes and then continued after stopping for 3 minutes.

[0045] Preferably, in step (2), during ball milling, both the grinding jar and the grinding balls are made of tungsten carbide cemented carbide.

[0046] Preferably, in step (2), during ball milling, the mill is stopped every 10 minutes and then continued to run after stopping for 2 minutes.

[0047] Preferably, in step (3), during sintering, the heating rate is 100 to 150° C. / min.

[0048] Example 1

[0049] (1) Weigh 60.0 g of Fe3Al and 40.0 g of TiC powder, both of which are 200 mesh, and ball mill them under argon protection. Add 2 ml of ethanol before ball milling. The ball-to-material ratio is 3:1. The speed is 250 r / min. The ball milling time is 8 h. Stop once every 5 min and continue to run after stopping for 3 min. Put the mixed powder into a graphite mold and place it in a spark plasma sintering furnace for sintering. The vacuum degree is less than 1×10 -1 Pa, heating rate 100℃ / min, sintering temperature 1100℃, holding time 5min, cooling to room temperature with the furnace, crushing the cooled loose block, and grinding it in a high-energy ball mill under the protection of inert gas, with a ball-to-material ratio of 1:1, a rotation speed of 100r / min, and a ball milling time of 6h to obtain a composite strengthening phase powder (Fe3Al+TiC) of not less than 200 mesh.

[0050] (2) Weigh 75.0 g of Cu, 9.0 g of Al, 1.0 g of Ni, 3.5 g of Fe, 1.5 g of Mn, 1.0 g of Cr, 1.0 g of Y2O3, 3.0 g of composite strengthening phase (Fe3Al+TiC) powder, and 5.0 g of composite lubricating phase (2.0 g of NiMoO4+3.0 g of nickel-coated graphite balls), and mix them by low-energy ball milling. The grinding jar and grinding balls are both tungsten carbide cemented carbide, the ball-to-material ratio is 1:1, the rotation speed is 150 r / min, the ball milling time is 8 h, and the mill is stopped every 10 min. After stopping for 2 min, it continues to run. After the ball milling is completed, a mixed powder is obtained.

[0051] (3) placing the mixed powder in a spark plasma sintering furnace for hot pressing sintering with a vacuum degree of less than 1×10 - 1 Pa, heating rate of 110 ° C / min, sintering temperature of 800 ° C, applied pressure of 35 MPa, holding time of 10 min, cooling to room temperature with the furnace, to obtain an intermetallic compound reinforced shift friction plate material.

[0052] The material was tested for performance: the hardness was 211HV using a Vickers hardness tester. The mechanical properties were tested using a CMT-5205 universal material testing machine, with a compression and three-point bending displacement rate of 0.1mm / min. The material had a compressive strength of 1005MPa and a flexural strength of 883MPa.

[0053] The tribological properties were evaluated using a HT-1000 high temperature friction and wear tester. The dual ball was a 316 stainless steel ball, the load was 5N, the sliding speed was 0.15m / s, the friction radius was 5mm, the running time was 30min, and the test temperatures were 25℃ and 500℃, respectively. The test showed that the average friction coefficient of the material at room temperature was 0.28, and the average wear rate was 1.2×10 - 4 mm 3 / N·m; the average friction coefficient at 500℃ is 0.49, and the average wear rate is 5.1×10 -4 mm 3 / N·m, and has good anti-friction and anti-wear performance. It can be seen that the material has a low and stable friction coefficient and wear rate, and has good anti-friction and anti-wear performance.

[0054] Example 2

[0055] (1) Weigh 70.0 g of Fe3Al and 30.0 g of TiC powder, both of which are 200 mesh, and ball mill them under argon protection, with a ball-to-material ratio of 3.5:1, a rotation speed of 300 r / min, and a ball milling time of 10 h. Stop once every 5 min and continue to run after stopping for 3 min. Put the mixed powder into a graphite mold and place it in a spark plasma sintering furnace for sintering. The vacuum degree is less than 1×10 - 1 Pa, heating rate 130℃ / min, sintering temperature 1200℃, holding time 7min, cooling to room temperature with the furnace, crushing the cooled loose block, and grinding it in a high-energy ball mill under the protection of inert gas, with a ball-to-material ratio of 1.5:1, a rotation speed of 130r / min, and a grinding time of 7h to obtain a composite strengthening phase powder (Fe3Al+TiC) of not less than 200 mesh.

[0056] (2) Weigh 65.0 g of Cu, 12.0 g of Al, 2.5 g of Ni, 4.0 g of Fe, 0.5 g of Mn, 0.5 g of Cr, 0.5 g of Y2O3, 6.0 g of composite strengthening phase (Fe3Al+TiC) powder, and 9.0 g of composite lubricating phase (4.5 g of NiMoO4+4.5 g of nickel-coated graphite balls), and mix them by low-energy ball milling. The grinding jar and grinding balls are both made of tungsten carbide cemented carbide, the ball-to-material ratio is 1.5:1, the rotation speed is 170 r / min, the ball milling time is 9 h, and the mill is stopped every 10 min. After stopping for 2 min, the milling is continued. After the ball milling is completed, a mixed powder is obtained.

[0057] (3) placing the mixed powder in a spark plasma sintering furnace for hot pressing sintering with a vacuum degree of less than 1×10 - 1 Pa, heating rate 130℃ / min, sintering temperature 830℃, applied pressure 37MPa, holding time 15min, cooling to room temperature with the furnace, to obtain an intermetallic compound reinforced shift friction plate material.

[0058] The material was tested for performance using the same test method as in Example 1. Its hardness was 200 HV, its compressive strength was 956 MPa, and its flexural strength was 826 MPa. Its average friction coefficient at room temperature was 0.24, and its average wear rate was 1.0×10 -4 mm 3 / N·m; the average friction coefficient at 500℃ is 0.42, and the average wear rate is 4.5×10 -4 mm 3 / N·m, and has good anti-friction and anti-wear performance. It can be seen that the material has a low and stable friction coefficient and wear rate, and has good anti-friction and anti-wear performance.

[0059] Example 3

[0060] (1) Weigh 80.0 g of Fe3Al and 20.0 g of TiC powder, both of which are 200 mesh, and ball mill them under argon protection, with a ball-to-material ratio of 4:1, a rotation speed of 350 r / min, and a ball milling time of 12 h. Stop once every 5 min and continue to run after stopping for 3 min. Put the mixed powder into a graphite mold and place it in a spark plasma sintering furnace for sintering. The vacuum degree is less than 1×10 - 1 Pa, heating rate 150℃ / min, sintering temperature 1300℃, holding time 10min, cooling to room temperature with the furnace, crushing the cooled loose block, and grinding it in a high-energy ball mill under the protection of inert gas, with a ball-to-material ratio of 2:1, a rotation speed of 150r / min, and a ball milling time of 8h to obtain a composite strengthening phase powder (Fe3Al+TiC) of not less than 200 mesh.

[0061] (2) Weigh 63.0 g of Cu, 9.0 g of Al, 1.9 g of Ni, 4.0 g of Fe, 1.5 g of Mn, 0.3 g of Cr, 0.3 g of Y2O3, 8.0 g of composite strengthening phase (Fe3Al+TiC) powder, and 12.0 g of composite lubricating phase (4.8 g of NiMoO4+7.2 g of nickel-coated graphite balls), and mix them by low-energy ball milling. The grinding jar and grinding balls are both made of tungsten carbide cemented carbide, the ball-to-material ratio is 1.5:1, the rotation speed is 170 r / min, the ball milling time is 9 h, and the mill is stopped every 10 min. After stopping for 2 min, it continues to run. After the ball milling is completed, a mixed powder is obtained.

[0062] (3) placing the mixed powder in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 - 1 Pa, heating rate 100 ℃ / min, sintering temperature 850 ℃, applied pressure 40MPa, holding time 20min, cooling to room temperature with the furnace, to obtain an intermetallic compound reinforced shift friction plate material.

[0063] The material was tested for performance using the same test method as in Example 1. Its hardness was 192 HV, its compressive strength was 893 MPa, and its flexural strength was 755 MPa. Its average friction coefficient at room temperature was 0.20, and its average wear rate was 0.8×10 -4 mm 3 / N·m; the average friction coefficient at 500℃ is 0.37, and the average wear rate is 4.0×10 -4 mm 3 / N·m, and has good anti-friction and anti-wear performance. It can be seen that the material has a low and stable friction coefficient and wear rate, and has good anti-friction and anti-wear performance.

[0064] Comparative Example 1

[0065] Compared with Example 3, the composite strengthening phase (Fe3Al+TiC) is replaced by TiC in Comparative Example 1, and the mass is the same as 8.0g. The other material components, contents, and preparation processes are consistent with those in Example 3. The material properties obtained in Comparative Example 1 are compared with those in Example 3 (Table 1). The results show that the compressive strength and flexural strength of Comparative Example 1 decrease, and the wear rate increases. This is because when the composite strengthening phase is all TiC, the bonding force between the strengthening phase and the matrix interface decreases, which in turn causes the strength and wear resistance to decrease.

[0066] Table 1 Comparison of Comparative Example 1 with Example 3

[0067]

[0068] Comparative Example 2

[0069] Compared with Example 3, the composite strengthening phase (Fe3Al+TiC) is replaced with Fe3Al in Comparative Example 2, and the mass is the same as 8.0g. The other material components, contents, and preparation processes are consistent with those in Example 3. The material properties obtained in Comparative Example 2 are compared with those in Example 3 (Table 2). The results show that the hardness, compressive strength, and flexural strength of Comparative Example 2 decrease, and the wear rate increases. This is because when TiC is missing, the high chemical energy mixed powder of (Fe3Al+TiC) cannot be obtained, and the strengthening effect of TiC on high aluminum bronze cannot be produced, which results in a decrease in hardness, strength, and wear resistance.

[0070] Table 2 Comparison of Comparative Example 2 with Example 3

[0071]

[0072]

[0073] Comparative Example 3

[0074] Compared with Example 2, Comparative Example 2 replaces the composite lubricating phase (NiMoO4+nickel-coated graphite balls) with NiMoO4, and the mass is the same as 9.0g. Other material components, contents, and preparation processes are consistent with those of Example 2. The material properties obtained in Comparative Example 3 are compared with those in Example 2 (Table 3). The results show that the compressive strength and flexural strength of Comparative Example 3 decrease. This is because the interface bonding force between NiMoO4 and the aluminum bronze matrix is ​​lower than the interface bonding force between the nickel-coated graphite balls and the aluminum bronze matrix. When the content of NiMoO4 is too much, cracks are prone to initiation and expansion at the grain boundaries of the material, resulting in a decrease in strength.

[0075] Table 3 Comparison of Comparative Example 3 with Example 2

[0076]

[0077] Comparative Example 4

[0078] Compared with Example 2, Comparative Example 4 replaces the composite lubricating phase (NiMoO4+nickel-coated graphite balls) with nickel-coated graphite balls, and the mass is the same as 9.0g. Other material components, contents, and preparation processes are consistent with those of Example 2. The material properties obtained in Comparative Example 4 are compared with those in Example 2 (Table 4). The results show that the friction coefficient and wear rate of Comparative Example 4 increase at 500°C. This is because the lubricating effect of nickel-coated graphite balls is weaker than that of NiMoO4 in a high temperature environment. When the material does not contain NiMoO4, the lubricating ability at high temperature decreases, resulting in an increase in the friction coefficient and aggravated wear.

[0079] Table 4 Comparison of Comparative Example 4 with Example 2

[0080]

[0081] Comparative Example 5

[0082] Compared with Example 3, the composite strengthening phase and composite lubricating phase contained in Comparative Example 5 exceed the specified range, and the content of aluminum bronze matrix is ​​lower than the specified range. The specific composition ratio is 61.0g of Cu, 5.0g of Al, 2.0g of Ni, 4.0g of Fe, 1.0g of Mn, 1.0g of Cr, 1.0g of Y2O3, 10.0g of (Fe3Al+TiC), and 15.0g of (NiMoO4+nickel-coated graphite balls). Other preparation processes and process parameters are consistent with those of Example 3. The material properties obtained in Comparative Example 5 are compared with those in Example 3 (Table 5). The results show that the hardness, compressive strength, flexural strength, and friction coefficient of Comparative Example 5 decrease, and the wear rate increases. This is because when the amount of composite strengthening phase and composite lubricating phase added is too much, although the friction coefficient can be reduced, there are too many impurities and defects at the grain boundaries of the material, and the internal phase interface bonding force decreases, resulting in a decrease in strength.

[0083] Table 5 Comparison of Comparative Example 5 with Example 3

[0084]

[0085] Comparative Example 6

[0086] Compared with Example 1, the Cu content in Comparative Example 6 is lower than the specified range, and the Al content is higher than the specified range. The specific composition ratio is 62.0g of Cu, 22.0g of Al, 1.0g of Ni, 3.5g of Fe, 1.5g of Mn, 1.0g of Cr, 1.0g of Y2O3, 3.0g of composite strengthening phase (Fe3Al+TiC) powder, and 5.0g of composite lubricating phase (2.0g of NiMoO4+3.0g of nickel-coated graphite balls). Other preparation processes and process parameters are consistent with those of Example 1. The material properties obtained in Comparative Example 6 are compared with those in Example 1 (Table 6). The results show that the compressive strength and flexural strength of Comparative Example 6 decrease, and the wear rate increases. This is because when there is too much Al and too little Cu in the matrix, the α phase with excellent ductility in the material organization decreases, and the irregular, hard β phase and γ phase increase, which then leads to a decrease in material strength and wear resistance.

[0087] Table 6 Comparison of Comparative Example 6 with Example 1

[0088]

[0089] Comparative Example 7

[0090] Compared with Example 1, Cr and Y2O3 are not added in Comparative Example 7, and the specific composition ratio of the material is: 77.0g of Cu, 9.0g of Al, 1.0g of Ni, 3.5g of Fe, 1.5g of Mn, 3.0g of composite strengthening phase (Fe3Al+TiC) powder, 5.0g of composite lubricating phase (2.0g of NiMoO4+3.0g of nickel-coated graphite balls). Other preparation processes and process parameters are consistent with those of Example 1. The material properties obtained in Comparative Example 7 are compared with those in Example 1 (Table 7). The results show that the hardness, compressive strength and flexural strength of Comparative Example 7 decrease, and the wear rate increases. This is because when Cr and Y2O3 are missing, the refinement and dispersion strengthening effects cannot be produced, the hardness and strength of the material decrease, resulting in reduced wear resistance.

[0091] Table 7 Comparative Example 7 compared with Example 1

[0092]

[0093] Comparative Example 8

[0094] Compared with Example 3, Comparative Example 8 did not perform high-energy ball milling and high-temperature sintering when preparing the composite strengthening phase (Fe3Al+TiC) powder, but only mixed by low-energy ball milling. The ball milling process is as follows: dry ball milling under argon protective atmosphere, ball-to-material ratio 1:1, rotation speed of 100r / min, stop once every 15min, stop 2min and continue ball milling, and the ball milling time is 8h. Other material components, contents, and preparation processes are consistent with those of Example 3. The material properties obtained in Comparative Example 8 are compared with those in Example 3 (Table 8), and the results show that the strength and wear resistance of the material obtained in Comparative Example 8 are reduced. This is because Comparative Example 8 did not perform high-energy ball milling and high-temperature sintering, resulting in a low degree of mutual solubility between Fe3Al and TiC, and TiC cannot have a strengthening effect on Fe3Al. At the same time, the dispersion and surface chemical energy of Fe3Al and TiC powders are low, and the bonding force with the aluminum bronze matrix is ​​reduced, so the material strength and wear resistance are reduced.

[0095] Table 8 Comparative Example 8 compared with Example 3

[0096]

[0097] Comparative Example 9

[0098] Compared with Example 1, when hot pressing and sintering are used to prepare the composite material in Comparative Example 9, the sintering temperature is higher than the specified range and the sintering pressure is lower than the specified range. The specific sintering process is as follows: the sintering temperature is 920°C, the pressure is 30MPa, the constant temperature and pressure are maintained for 5 minutes, the hot pressing sintering is terminated, and the furnace is cooled to room temperature. Other material components, contents, and preparation processes are consistent with those in Example 1. The material properties obtained in Comparative Example 9 are compared with those in Example 1 (Table 9). The results show that the hardness and strength of the material obtained in Comparative Example 9 decrease, and the wear rate increases. This is because the sintering temperature of Comparative Example 9 is too high, which causes the phase composition of the high-aluminum bronze matrix to change, and the finished product segregates, and the α phase and κ phase formed by Cu and Al are uneven. At the same time, the sintering pressure of Comparative Example 9 is too low, which causes the density, hardness and strength of the material to decrease.

[0099] Table 9 Comparative Example 9 compared with Example 1

[0100]

[0101] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.

Claims

1. A gear shift friction plate material reinforced by an intermetallic compound, characterized in that: Taking the total mass of the material as 100%, the components and their mass percentages are: 80.0% to 92.0% of high-aluminum bronze matrix, 3.0% to 8.0% of composite strengthening phase, and 5.0% to 12.0% of composite lubricating phase; wherein the composite strengthening phase is formed by compounding Fe3Al and TiC through high-energy ball milling, the mass fraction of Fe3Al in the composite strengthening phase is 60.0% to 80.0%, and the mass fraction of TiC is 20.0% to 40.0%; the composite lubricating phase is formed by compounding NiMoO4 and nickel-coated graphite balls, the mass fraction of NiMoO4 in the composite lubricating phase is 40.0% to 60.0%, and the mass fraction of nickel-coated graphite balls is 40.0% to 60.0%; the material is obtained by ball milling and hot-pressing sintering of an aluminum bronze matrix, a composite strengthening phase and a composite lubricating phase; Taking the total mass of the material as 100%, the components and their mass percentages are: Cu63.0%-75.0%, Al 9.0%-13.0%, Ni 1.0%-2.5%, Fe 2.5%-4.0%, Mn 0.5%-1.5%, Cr 0.3%-1.0%, Y2O3 0.3%-1.0%, composite strengthening phase 3.0%-8.0%, composite lubricating phase 5.0%-12.0%; The preparation method of the material comprises the following steps: (1) Fe3Al and TiC powders are mixed and wet-milled under inert gas protection, with a ball-to-material ratio of 3:1 to 4:1, a rotation speed of 250 to 350 r / min, and a ball milling time of 8 to 12 h to obtain a mixed powder, and the mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1 Pa, sintering temperature is 1100-1300℃, holding time is 5-10min, after sintering, the furnace is cooled, and the obtained block is ground under the protection of inert gas to obtain composite strengthening phase powder; (2) mixing the aluminum bronze matrix, the composite strengthening phase powder and the composite lubricating phase powder, and ball milling them under inert gas protection, with a ball-to-material ratio of 1:1 to 2:1, a rotation speed of 150 to 200 r / min, and a ball milling time of 8 to 10 h to obtain a mixed powder; (3) The mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1 Pa, the sintering temperature is 800-850°C, the sintering pressure is 35-40MPa, the holding time is 10-20min, and the furnace is cooled after sintering to obtain an intermetallic compound reinforced shift friction plate material.

2. The intermetallic compound reinforced shift friction plate material according to claim 1, characterized in that: The mesh size of the composite reinforcement phase powder is 200-300 meshes.

3. The intermetallic compound reinforced shift friction plate material according to claim 1, characterized in that: The mesh size of the NiMoO4 powder is 200-300 meshes.

4. The intermetallic compound reinforced shift friction plate material according to claim 1, characterized in that: The particle size of the nickel-coated graphite balls is 10 to 30 μm.

5. The intermetallic compound reinforced shift friction plate material according to claim 1, characterized in that: In step (1), the heating rate is 100-150°C / min.

6. The intermetallic compound reinforced shift friction plate material according to claim 1, characterized in that: In step (1), during grinding, the grinding jar and the grinding balls are both made of tungsten carbide, the ball-to-material ratio is 1:1-2:1, the rotation speed is 100-150 r / min, and the grinding time is 6-8 h; the grinding is stopped every 10 min, and the operation is continued after stopping for 2 min.

7. The intermetallic compound reinforced shift friction plate material according to claim 1, characterized in that: In step (2), during ball milling, the grinding jar and the grinding balls are both made of tungsten carbide hard alloy; the process is stopped every 10 minutes, and the process is continued after stopping for 2 minutes.

8. The intermetallic compound reinforced shift friction plate material according to any one of claims 1 or 5 to 7, characterized in that: In step (3), during sintering, the heating rate is 100-150°C / min.

Citation Information

Patent Citations

  • High-strength antifriction and wearable aluminum-manganese bronze alloy

    CN104388749A

  • Copper-aluminum-iron-nickel-manganese-chromium-silicon alloy capable of improving wear-resistant performance

    CN105088004A

  • A copper-iron-based braking composite material and its preparation method

    CN106086585B

  • A nano-carbon reinforced copper matrix composite material for maglev trains and its preparation method

    CN108517435B

  • Rare-earth-doped aluminum bronze and preparation method thereof

    CN112195361A